Processing technology of ultrathin semiconductor lead frame
By using copper, nickel, silicon and other materials to melt into a copper alloy in the processing process of semiconductor lead frames, and adding high-melting point alloys to wrap low-melting point alloy particles as refining agents, combined with specific treatment liquids, the problem of easy deformation and corrosion of the lead frame is solved, and the effect of high mechanical properties and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411798859.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-25
AI Technical Summary
The existing ultra-thin semiconductor lead frames are prone to deformation or damage during stamping preparation, and are susceptible to invasion of water vapor and cause corrosion, with a low yield rate.
Copper, nickel, silicon and other materials are melted under an inert gas atmosphere to form a copper alloy, high-melting point alloy is added to wrap low-melting point alloy particles as a refining agent, and treated with a specific treatment liquid to improve corrosion resistance.
It significantly improves the mechanical properties and corrosion resistance of the semiconductor lead frame, reduces the risk of deformation and corrosion, and improves the yield rate.
Abstract
Description
Technical Field
[0002] The invention relates to the technical field of semiconductor packaging, in particular to a processing technology for an ultra-thin semiconductor lead frame. Background Art
[0004] The semiconductor lead frame is a thin metal frame used to connect the contact points of the internal chip of the semiconductor integrated block and the external wires. It is a major structural material for semiconductor packaging. It is mainly composed of chip pads and pins. As the chip carrier of the integrated circuit, the lead frame uses bonding materials (such as gold wire, aluminum wire, copper wire) to make the internal circuit lead end (bonding point) of the chip electrically connected to the external lead through the inner lead to form an electrical circuit, which plays the role of a bridge connecting with the external wires. In the integrated circuit, the lead frame and the packaging material play the role of fixing the chip, protecting the internal components, transmitting electrical signals, and dissipating the heat of the components to the outside.
[0005] However, in the prior art, some ultra-thin semiconductor lead frames often have poor material mechanical properties, which causes the lead frames to deform or be damaged during the stamping process, resulting in a low yield rate; during the lead frame packaging process, water vapor can easily enter the interior of the product, causing product failure or easy corrosion of the frame.
[0006] In summary, in order to solve the above problems, it is of great significance to provide a semiconductor lead frame processing technology with good mechanical properties and strong corrosion resistance. Summary of the invention
[0008] The purpose of the present invention is to provide a processing technology for an ultra-thin semiconductor lead frame to solve the problems raised in the prior art.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A processing technology for an ultra-thin semiconductor lead frame comprises the following steps:
[0011] S1: In an inert gas atmosphere, grind copper, nickel and silicon separately, pass through a 800-1000 mesh sieve, mix evenly, and smelt at 1600-1650°C for 30-60 minutes to obtain molten metal;
[0012] S2: In an inert gas atmosphere, add a refiner, stir electromagnetically for 2-3 minutes, take out of the furnace at 1550-1600°C, pour into a ladle for slagging, pour, demould, anneal, and cool to room temperature to obtain a copper alloy ingot;
[0013] S3: heating the copper alloy ingot to 850-900° C., hot rolling, cooling to room temperature, cold rolling, heat treating at 400-450° C. for 1.5-2.5 h, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0014] S4: After degreasing the crude semiconductor lead frame, spray it with an organic acid solution for 25 to 35 seconds, rinse it with a 2 to 3% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution to react for 10 to 15 minutes, add tris(3-aminopropyl)amine, react for 1.5 to 2 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0015] Preferably, the mass ratio of copper, nickel and silicon is 95-97:1.5-2.5:0.5.
[0016] Preferably, the organic pickling solution comprises the following substances: 52-56 g / L copper acetate, 50-52 g / L ammonium chloride, 70-74 g / L sodium formate, 8-10 g / L sodium citrate, 20-22 mL / L glacial acetic acid, 11-12 mL / L formic acid, and the solvent is deionized water.
[0017] Preferably, the treatment liquid comprises the following substances: 30~32g / L 18-mercaptooctadecanoic acid, 15~17g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 13~15g / L N-hydroxysuccinimide, and the solvent is deionized water: the concentration of the added tris(3-aminopropyl)amine in the treatment liquid is 5~7g / L.
[0018] Wherein, during the hot rolling process, the final rolling temperature is 700-750°C; during the cold rolling process, the deformation amount is 30-40%, and the number of cold rolling times is 2 times.
[0019] Preferably, the amount of the refiner added is 1-2wt% of the total mass of copper, nickel and silicon; the preparation of the refiner comprises the following steps:
[0020] (1) In an inert gas atmosphere, cerium, magnesium, titanium and aluminum are mixed uniformly, heated to melt, cast, demolded, kept at 400-500°C for 1-2 hours, cooled to room temperature, crushed and ground to obtain alloy particles;
[0021] (2) mixing polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water, and stirring at 50-70° C. for 2-3 hours to obtain an organic binder;
[0022] (3) Mix and grind the copper-tungsten alloy, boron trioxide and boron powder, and pass through an 800-mesh sieve to obtain metal powder;
[0023] (4) spraying the organic binder on the surface of the alloy particles, adding it to the metal powder, mixing, compacting and screening, and repeating the operation until a refiner precursor with a mass ratio of metal powder to alloy particles of 3:7-8 is obtained;
[0024] (5) The refiner precursor is kept at 80-90°C in an inert gas atmosphere for 1-2 hours, cooled, added to 50-60°C deionized water and soaked for 4-5 hours, dried, kept at 400-450°C in an inert gas flow for 30-40 minutes, and finally sintered at 550-650°C in a vacuum or inert gas atmosphere for 20-40 minutes to obtain the refiner.
[0025] The alloy particles include cerium, magnesium, titanium and aluminum in a mass ratio of 1:3.5~4.5:1.8~2.2:2.5~3.5; and the particle size of the alloy particles is 3~5 mm.
[0026] Preferably, the organic binder comprises polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water in a mass ratio of 3~5:2~4:18~22:24~26:30; the metal powder comprises copper tungsten alloy, boron powder and boron trioxide in a mass ratio of 75:5~10:15~20.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The semiconductor lead frame processed by the present invention is a copper alloy obtained by smelting copper, nickel and silicon. A certain proportion of nickel is added to the alloy to form a continuous solid solution with copper, which can significantly improve the strength of the alloy and reduce the temperature coefficient of resistivity. However, when the amount of nickel added is large, the mechanical properties of the alloy can be further improved, but the electrical conductivity will decrease. Adding a small amount of silicon can stabilize the grain structure of the copper alloy at high temperature, avoid grain growth, and improve the mechanical properties of the alloy. However, adding too much silicon will cause the material to self-crack, making it difficult to use. In order to further improve the mechanical properties, the present invention also adds alloy particles containing cerium, magnesium, titanium and aluminum as a refiner during the smelting process to refine the particles in the alloy and improve the mechanical properties: cerium, as a rare earth element, can form stable compounds with copper. In the alloy, copper will use these compounds as dispersed crystal cores to refine the grains, but if too much is added, too many compounds will be formed, reducing the supercooling effect of the rare earth atoms, and the alloy particles will be coarsened instead. Therefore, the present invention controls the cerium content to be about 0.1wt%; titanium and aluminum can generate square lattice TiAl3, copper can use this as a substrate for growth, and play a role in refining the grains; at the same time, aluminum and magnesium are excellent deoxidizers, which reduce the oxygen content in the alloy and reduce the impact on the mechanical properties and conductivity of the alloy. However, the ultra-thin lead frame of the present invention has a high overheating rate, and the melting and casting temperatures are close to 1600°C. After the addition of low-melting-point elements such as cerium and aluminum, they are easily melted to form alloy elements, which cannot play a role in refining the grains. In particular, cerium is easy to float during the refinement process. In addition, the temperature is high and the probability of oxidation and burning is high, so the refinement effect is limited. Therefore, the present invention adds elements with higher melting points, boron and tungsten, to the surface of the alloy particles to effectively prevent the problem of failure of the refiner due to high temperature. The present invention uses copper-tungsten alloy powder, boron trioxide, and boron powder to grind and mix, and uses an organic binder to fix the metal powder on the surface of the alloy particles. After solidification, the aqueous substance is washed away with water, and most of the polymethyl methacrylate is removed under an airflow of 400~450°C. Finally, the alloy particles are sintered to obtain the effect of high-melting-point elements wrapping the alloy particles: the aqueous substance in the organic adhesive of the present invention is mainly low-molecular-weight polyethylene glycol, which is easily dissolved and removed by water after solidification, greatly reducing the oxygen content in the refiner and reducing the impact on the alloy; polymethyl methacrylate is used as an organic skeleton after the binder is solidified. Most of the carbon is removed under high-temperature airflow, and the residual carbon can form WC with tungsten, which can play a role in refining the grains; the added boron can improve the strength of the alloy, and can also hinder the growth of grains and reduce the interface energy, thereby refining the crystals, but the boron content should not be too much, which will lead to excessive formation of borides and reduce the mechanical properties; at the same time, the present invention also adds boron oxide, which has a low melting point of only 450°C. In the process of removing polymethyl methacrylate, boron oxide can make preliminary connections between metal particles, thereby better wrapping the low-melting-point alloy particles and reducing the possibility of failure of the refiner.
[0029] (2) The present invention uses a specific proportion of treatment liquid to roughen the surface of the lead frame, so as to improve the bonding degree between the lead frame and the organic packaging material: the main components of the treatment liquid of the present invention are organic acid and corrosion inhibitor, which can evenly corrode the surface of the frame, and the surface treatment is carried out by spraying the treatment liquid. The degree of roughening can be controlled by controlling the water pressure and time. At the same time, the present invention adds the roughened lead frame to the treatment liquid containing 18-mercaptooctadecanoic acid for treatment. The mercapto group will react with the active copper in the surface roughening holes to form a chemical bond, and the long chain part will self-assemble into a film on the surface of the lead frame, which can greatly improve the corrosion resistance of the lead frame. In addition, the present invention also adds tris(3-aminopropyl)amine to the treatment liquid. The amino group on the end group of the branched structure will form a chemical bond with the carboxyl group, so that the film formed by the self-assembly of the long carbon chain on the surface is more uniform, thereby further improving the film-forming effect and improving the corrosion resistance of the lead frame. DETAILED DESCRIPTION
[0031] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0032] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and exemplarily include: cerium; magnesium; titanium; aluminum; polyethylene glycol diacrylate, cas: 26570-48-9; oleic acid; polyethylene glycol, molecular weight 1000; polymethyl methacrylate, molecular weight 10000; copper tungsten alloy, specification: CuW70; boron trioxide; boron powder; copper; nickel; silicon; copper acetate; ammonium chloride; sodium formate; sodium citrate; glacial acetic acid; formic acid; 18-mercaptooctadecanoic acid, cas: 600730-11-8; tris (3-aminopropyl) amine, cas: 4963-47-7, all of which are commercially available.
[0033] Example 1: Step 1: Preparation of thinning agent:
[0034] (1) Under an inert gas atmosphere, cerium, magnesium, titanium and aluminum are uniformly mixed in a mass ratio of 1:4:2:3, heated to melt, cast, demolded, kept at 450°C for 1.5 hours, cooled to room temperature, crushed, and ground to a particle size of 4 mm to obtain alloy particles;
[0035] (2) polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water were mixed in a mass ratio of 4:3:20:25:30, and stirred at 60° C. for 2.5 h to obtain an organic binder;
[0036] (3) Mix and grind copper-tungsten alloy, boron trioxide and boron powder in a mass ratio of 75:7.5:17, and pass through an 800-mesh sieve to obtain metal powder;
[0037] (4) spraying an organic binder on the surface of the alloy particles, adding it to the metal powder, mixing, compacting and screening, and repeating the operation until a refiner precursor having a mass ratio of metal powder to alloy particles of 3:7 is obtained;
[0038] (5) The refiner precursor is kept at 85°C in an inert gas atmosphere for 1.5 hours, cooled, immersed in 55°C deionized water for 4.5 hours, dried, kept at 425°C in an inert gas flow for 35 minutes, and then sintered at 600°C for 30 minutes in a vacuum or inert gas atmosphere to obtain a refiner;
[0039] Step 2: Preparation of semiconductor lead frame:
[0040] S1: In an inert gas atmosphere, copper, nickel and silicon are ground respectively in a mass ratio of 96:2:0.5, passed through an 800-mesh sieve, mixed evenly, and smelted at 1650°C for 45 minutes to obtain a molten metal;
[0041] S2: In an inert gas atmosphere, add a refiner of 1.5wt% of the total mass of copper, nickel and silicon, stir with electromagnetic stirring for 2.5min, take out of the furnace at 1575℃, pour into a ladle, slag, pour, demould, anneal, and cool to room temperature to obtain a copper alloy ingot;
[0042] S3: heating the copper alloy ingot to 875°C, hot rolling, and the final rolling temperature is 725°C; cooling to room temperature, cold rolling with a deformation amount of 35%, heat treatment at 425°C for 2h, repeating twice, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0043] S4: After degreasing the crude semiconductor lead frame, spray it with an organic pickling solution (54 g / L copper acetate, 51 g / L ammonium chloride, 72 g / L sodium formate, 9 g / L sodium citrate, 21 mL / L glacial acetic acid, 11 mL / L formic acid, and the solvent is deionized water) for 30 seconds, then rinse it with a 2.5% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution (31 g / L 18-mercaptooctadecanoic acid, 16 g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 14 g / L N-hydroxysuccinimide, and the solvent is deionized water) and react for 10 minutes. Add tri(3-aminopropyl)amine to make its concentration in the treatment solution 6 g / L, react for 1.5 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0044] Example 2: Step 1: Preparation of thinning agent:
[0045] (1) Under an inert gas atmosphere, cerium, magnesium, titanium and aluminum are uniformly mixed in a mass ratio of 1:4:2:3, heated to melt, cast, demolded, kept at 450°C for 1.5 hours, cooled to room temperature, crushed, and ground to a particle size of 4 mm to obtain alloy particles;
[0046] (2) polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water were mixed in a mass ratio of 4:3:20:25:30, and stirred at 60° C. for 2.5 h to obtain an organic binder;
[0047] (3) Mix and grind copper-tungsten alloy, boron trioxide and boron powder in a mass ratio of 75:7.5:17, and pass through an 800-mesh sieve to obtain metal powder;
[0048] (4) spraying an organic binder on the surface of the alloy particles, adding it to the metal powder, mixing, compacting and screening, and repeating the operation until a refiner precursor having a mass ratio of metal powder to alloy particles of 3:7 is obtained;
[0049] (5) The refiner precursor is kept at 85°C in an inert gas atmosphere for 1.5 hours, cooled, immersed in 55°C deionized water for 4.5 hours, dried, kept at 425°C in an inert gas flow for 35 minutes, and then sintered at 600°C for 30 minutes in a vacuum or inert gas atmosphere to obtain a refiner;
[0050] Step 2: Preparation of semiconductor lead frame
[0051] S1: In an inert gas atmosphere, copper, nickel and silicon are ground respectively in a mass ratio of 97:2.5:0.5, passed through an 800-mesh sieve, mixed evenly, and smelted at 1650°C for 60 minutes to obtain a molten metal;
[0052] S2: In an inert gas atmosphere, add a refiner of 2 wt% of the total mass of copper, nickel and silicon, stir electromagnetically for 3 minutes, take out of the furnace at 1600°C, pour into a ladle for slagging, pour, demould, anneal, and cool to room temperature to obtain a copper alloy ingot;
[0053] S3: heating the copper alloy ingot to 900°C, hot rolling, and the final rolling temperature is 750°C; cooling to room temperature, cold rolling twice with a deformation amount of 40%, heat treating at 450°C for 2.5h, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0054] S4: After degreasing the crude semiconductor lead frame, spray it with an organic pickling solution (56 g / L copper acetate, 52 g / L ammonium chloride, 74 g / L sodium formate, 10 g / L sodium citrate, 22 mL / L glacial acetic acid, 12 mL / L formic acid, and the solvent is deionized water) for 35 seconds, then rinse it with a 3% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution (32 g / L 18-mercaptooctadecanoic acid, 17 g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 15 g / L N-hydroxysuccinimide, and the solvent is deionized water) and react for 15 minutes. Add tri(3-aminopropyl)amine to make its concentration in the treatment solution 7 g / L, react for 2 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0055] Example 3: Step 1: Preparation of thinning agent:
[0056] (1) Under an inert gas atmosphere, cerium, magnesium, titanium and aluminum are uniformly mixed in a mass ratio of 1:4:2:3, heated to melt, cast, demolded, kept at 450°C for 1.5 hours, cooled to room temperature, crushed, and ground to a particle size of 4 mm to obtain alloy particles;
[0057] (2) polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water were mixed in a mass ratio of 4:3:20:25:30, and stirred at 60° C. for 2.5 h to obtain an organic binder;
[0058] (3) Mix and grind copper-tungsten alloy, boron trioxide and boron powder in a mass ratio of 75:7.5:17, and pass through an 800-mesh sieve to obtain metal powder;
[0059] (4) spraying an organic binder on the surface of the alloy particles, adding it to the metal powder, mixing, compacting and screening, and repeating the operation until a refiner precursor having a mass ratio of metal powder to alloy particles of 3:7 is obtained;
[0060] (5) The refiner precursor is kept at 85°C in an inert gas atmosphere for 1.5 hours, cooled, immersed in 55°C deionized water for 4.5 hours, dried, kept at 425°C in an inert gas flow for 35 minutes, and then sintered at 600°C for 30 minutes in a vacuum or inert gas atmosphere to obtain a refiner;
[0061] Step 2: Preparation of semiconductor lead frame
[0062] S1: In an inert gas atmosphere, copper, nickel and silicon are ground respectively in a mass ratio of 95:1.5:0.5, passed through an 800-mesh sieve, mixed evenly, and smelted at 1600°C for 30 minutes to obtain a molten metal;
[0063] S2: In an inert gas atmosphere, add a refiner of 1 wt% of the total mass of copper, nickel and silicon, stir electromagnetically for 2 minutes, take out of the furnace at 1550°C, pour into a ladle, slag, cast, demould, anneal, and cool to room temperature to obtain a copper alloy ingot;
[0064] S3: heating the copper alloy ingot to 850°C, hot rolling, and the final rolling temperature is 700°C; cooling to room temperature, cold rolling twice with a deformation amount of 30%, heat treating at 400°C for 1.5h, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0065] S4: After degreasing the crude semiconductor lead frame, spray it with an organic pickling solution (52 g / L copper acetate, 50 g / L ammonium chloride, 70 g / L sodium formate, 8 g / L sodium citrate, 20 mL / L glacial acetic acid, 11 mL / L formic acid, and the solvent is deionized water) for 25 seconds, then rinse it with a 2% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution (30 g / L 18-mercaptooctadecanoic acid, 15 g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 13 g / L N-hydroxysuccinimide, and the solvent is deionized water) and react for 10 minutes. Add tri(3-aminopropyl)amine to make its concentration in the treatment solution 5 g / L, react for 1.5 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0066] Comparative Example 1: Based on Example 1, during the preparation of the refiner, the alloy particles were not wrapped, and the alloy powder and alloy particles were directly added during the smelting process. The rest of the process remained unchanged, as follows:
[0067] Step 1: Preparation of refiner:
[0068] (1) Under an inert gas atmosphere, cerium, magnesium, titanium and aluminum are uniformly mixed in a mass ratio of 1:4:2:3, heated to melt, cast, demolded, kept at 450°C for 1.5 hours, cooled to room temperature, crushed, and ground to a particle size of 4 mm to obtain alloy particles;
[0069] (2) Mix copper-tungsten alloy, boron trioxide and boron powder in a mass ratio of 75:7.5:17 and grind them, and pass them through an 800-mesh sieve to obtain metal powder;
[0070] (3) mixing metal powder and alloy particles in a mass ratio of 3:7 to obtain a refining agent;
[0071] Step 2: Preparation of semiconductor lead frame:
[0072] S1: In an inert gas atmosphere, copper, nickel and silicon are ground respectively in a mass ratio of 96:2:0.5, passed through an 800-mesh sieve, mixed evenly, and smelted at 1650°C for 45 minutes to obtain a molten metal;
[0073] S2: In an inert gas atmosphere, add a refiner of 1.5wt% of the total mass of copper, nickel and silicon, stir with electromagnetic stirring for 2.5min, take out of the furnace at 1575℃, pour into a ladle, slag, pour, demould, anneal, and cool to room temperature to obtain a copper alloy ingot;
[0074] S3: heating the copper alloy ingot to 875°C, hot rolling, and the final rolling temperature is 725°C; cooling to room temperature, cold rolling with a deformation amount of 35%, heat treatment at 425°C for 2h, repeating twice, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0075] S4: After degreasing the crude semiconductor lead frame, spray it with an organic pickling solution (54 g / L copper acetate, 51 g / L ammonium chloride, 72 g / L sodium formate, 9 g / L sodium citrate, 21 mL / L glacial acetic acid, 11 mL / L formic acid, and the solvent is deionized water) for 30 seconds, then rinse it with a 2.5% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution (31 g / L 18-mercaptooctadecanoic acid, 16 g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 14 g / L N-hydroxysuccinimide, and the solvent is deionized water) and react for 10 minutes. Add tri(3-aminopropyl)amine to make its concentration in the treatment solution 6 g / L, react for 1.5 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0076] Comparative Example 2: Based on Example 1, no refiner is added, and the other processes remain unchanged, as follows: Step 1: Preparation of semiconductor lead frame:
[0077] S1: In an inert gas atmosphere, copper, nickel and silicon are ground respectively in a mass ratio of 96:2:0.5, passed through an 800-mesh sieve, mixed evenly, and smelted at 1650°C for 45 minutes to obtain a molten metal;
[0078] S2: In an inert gas atmosphere, the molten metal is taken out of the furnace at 1575°C, poured into a ladle for slagging, casting, demoulding, annealing, and cooling to room temperature to obtain a copper alloy ingot;
[0079] S3: heating the copper alloy ingot to 875°C, hot rolling, and the final rolling temperature is 725°C; cooling to room temperature, cold rolling with a deformation amount of 35%, heat treatment at 425°C for 2h, repeating twice, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0080] S4: After degreasing the crude semiconductor lead frame, spray it with an organic pickling solution (54 g / L copper acetate, 51 g / L ammonium chloride, 72 g / L sodium formate, 9 g / L sodium citrate, 21 mL / L glacial acetic acid, 11 mL / L formic acid, and the solvent is deionized water) for 30 seconds, then rinse it with a 2.5% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution (31 g / L 18-mercaptooctadecanoic acid, 16 g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 14 g / L N-hydroxysuccinimide, and the solvent is deionized water) and react for 10 minutes. Add tri(3-aminopropyl)amine to make its concentration in the treatment solution 6 g / L, react for 1.5 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0081] Comparative Example 3: Based on Example 1, the organic pickling solution was replaced with 15% sulfuric acid, and the rest of the process remained unchanged, as follows:
[0082] Step 1: Preparation of refiner:
[0083] (1) Under an inert gas atmosphere, cerium, magnesium, titanium and aluminum are uniformly mixed in a mass ratio of 1:4:2:3, heated to melt, cast, demolded, kept at 450°C for 1.5 hours, cooled to room temperature, crushed, and ground to a particle size of 4 mm to obtain alloy particles;
[0084] (2) polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water were mixed in a mass ratio of 4:3:20:25:30, and stirred at 60° C. for 2.5 h to obtain an organic binder;
[0085] (3) Mix and grind copper-tungsten alloy, boron trioxide and boron powder in a mass ratio of 75:7.5:17, and pass through an 800-mesh sieve to obtain metal powder;
[0086] (4) spraying an organic binder on the surface of the alloy particles, adding it to the metal powder, mixing, compacting and screening, and repeating the operation until a refiner precursor having a mass ratio of metal powder to alloy particles of 3:7 is obtained;
[0087] (5) The refiner precursor is kept at 85°C in an inert gas atmosphere for 1.5 hours, cooled, immersed in 55°C deionized water for 4.5 hours, dried, kept at 425°C in an inert gas flow for 35 minutes, and then sintered at 600°C for 30 minutes in a vacuum or inert gas atmosphere to obtain a refiner;
[0088] Step 2: Preparation of semiconductor lead frame:
[0089] S1: In an inert gas atmosphere, copper, nickel and silicon are ground respectively in a mass ratio of 96:2:0.5, passed through an 800-mesh sieve, mixed evenly, and smelted at 1650°C for 45 minutes to obtain a molten metal;
[0090] S2: In an inert gas atmosphere, add a refiner of 1.5wt% of the total mass of copper, nickel and silicon, stir with electromagnetic stirring for 2.5min, take out of the furnace at 1575℃, pour into a ladle, slag, pour, demould, anneal, and cool to room temperature to obtain a copper alloy ingot;
[0091] S3: heating the copper alloy ingot to 875°C, hot rolling, and the final rolling temperature is 725°C; cooling to room temperature, cold rolling with a deformation amount of 35%, heat treatment at 425°C for 2h, repeating twice, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0092] S4: After degreasing the crude semiconductor lead frame, spray it with 15% sulfuric acid for 30 seconds, rinse it with 2.5% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution (31g / L 18-mercaptooctadecanoic acid, 16g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 14g / L N-hydroxysuccinimide, and the solvent is deionized water) and react for 10 minutes. Add tri(3-aminopropyl)amine to make its concentration in the treatment solution 6g / L, react for 1.5 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0093] Comparative Example 4: Based on Example 1, tris(3-aminopropyl)amine was not added after the treatment solution was added for reaction, and the rest of the process remained unchanged, as follows:
[0094] Step 1: Preparation of refiner:
[0095] (1) Under an inert gas atmosphere, cerium, magnesium, titanium and aluminum are uniformly mixed in a mass ratio of 1:4:2:3, heated to melt, cast, demolded, kept at 450°C for 1.5 hours, cooled to room temperature, crushed, and ground to a particle size of 4 mm to obtain alloy particles;
[0096] (2) polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water were mixed in a mass ratio of 4:3:20:25:30, and stirred at 60° C. for 2.5 h to obtain an organic binder;
[0097] (3) Mix and grind copper-tungsten alloy, boron trioxide and boron powder in a mass ratio of 75:7.5:17, and pass through an 800-mesh sieve to obtain metal powder;
[0098] (4) spraying an organic binder on the surface of the alloy particles, adding it to the metal powder, mixing, compacting and screening, and repeating the operation until a refiner precursor having a mass ratio of metal powder to alloy particles of 3:7 is obtained;
[0099] (5) The refiner precursor is kept at 85°C in an inert gas atmosphere for 1.5 hours, cooled, immersed in 55°C deionized water for 4.5 hours, dried, kept at 425°C in an inert gas flow for 35 minutes, and then sintered at 600°C for 30 minutes in a vacuum or inert gas atmosphere to obtain a refiner;
[0100] Step 2: Preparation of semiconductor lead frame:
[0101] S1: In an inert gas atmosphere, copper, nickel and silicon are ground respectively in a mass ratio of 96:2:0.5, passed through an 800-mesh sieve, mixed evenly, and smelted at 1650°C for 45 minutes to obtain a molten metal;
[0102] S2: In an inert gas atmosphere, add a refiner of 1.5wt% of the total mass of copper, nickel and silicon, stir with electromagnetic stirring for 2.5min, take out of the furnace at 1575℃, pour into a ladle, slag, pour, demould, anneal, and cool to room temperature to obtain a copper alloy ingot;
[0103] S3: heating the copper alloy ingot to 875°C, hot rolling, and the final rolling temperature is 725°C; cooling to room temperature, cold rolling with a deformation amount of 35%, heat treatment at 425°C for 2h, repeating twice, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame;
[0104] S4: After degreasing the crude semiconductor lead frame, spray it with an organic pickling solution (54 g / L copper acetate, 51 g / L ammonium chloride, 72 g / L sodium formate, 9 g / L sodium citrate, 21 mL / L glacial acetic acid, 11 mL / L formic acid, and the solvent is deionized water) for 30 seconds, then rinse it with a 2.5% hydrochloric acid solution, and finally wash it with deionized water, dry it, and transfer it to a treatment solution (31 g / L 18-mercaptooctadecanoic acid, 16 g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 14 g / L N-hydroxysuccinimide, and the solvent is deionized water) to react for 1.5 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
[0105] Performance test: (1) According to GB / T 20254, the tensile strength of the lead frame of each embodiment was tested using a universal tensile testing machine. The experimental data are shown in Table 1. (2) According to GB / T10125 "Artificial atmosphere corrosion test salt spray test", a neutral salt spray test was performed on each embodiment, and the corrosion time was recorded. The experimental data are shown in Table 2.
[0106] Table 1
[0107] project Tensile strength / MPa Example 1 801 Example 2 782 Example 3 754 Comparative Example 1 702 Comparative Example 2 654
[0108] Table 2
[0109] project Corrosion time / h Example 1 45 Example 2 43 Example 3 42 Comparative Example 3 36 Comparative Example 4 32
[0110] Conclusion: It can be seen from Table 1 that in the preparation process of the refiner, in Comparative Example 1, the alloy particles are not wrapped, and the low-melting-point elements are easily melted to form alloy elements, which cannot refine the grains and reduce the tensile strength; in Comparative Example 2, no refiner is added, the alloy grains are large, the mechanical properties are poor, and the tensile strength is reduced; It can be seen from Table 2 that in Comparative Example 3, the organic pickling solution is replaced with sulfuric acid, the corrosion rate is faster, the corrosion uniformity is poor, and even after treatment with the treatment solution, the corrosion resistance is still reduced; in Comparative Example 4, no tri(3-aminopropyl)amine is added to react, and the film generated by the self-assembly of the long carbon chain on the surface is not uniform enough, and the corrosion resistance is reduced.
[0111] In summary, the present invention reduces the particle fineness in the alloy and improves the tensile strength of the semiconductor lead frame by adding a special refiner that wraps the low-melting-point alloy with a high-melting-point alloy during the alloy smelting process; improves the corrosion resistance by surface treatment of the semiconductor lead frame; and successfully provides a processing technology for an ultra-thin semiconductor lead frame.
[0112] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A processing technology for an ultra-thin semiconductor lead frame, characterized in that: The following steps are involved: S1: In an inert gas atmosphere, grind copper, nickel and silicon separately, pass through a 800-1000 mesh sieve, mix evenly, and smelt at 1600-1650°C for 30-60 minutes to obtain molten metal; S2: In an inert gas atmosphere, add a refiner, stir electromagnetically for 2-3 minutes, take out of the furnace at 1550-1600°C, pour into a ladle for slagging, pouring, demoulding, annealing, and cooling to room temperature to obtain a copper alloy ingot; S3: heating the copper alloy ingot to 850-900° C., hot rolling, cooling to room temperature, cold rolling, heat treating at 400-450° C. for 1.5-2.5 h, cooling to room temperature, stamping and slicing to obtain a rough semiconductor lead frame; S4: After degreasing the crude semiconductor lead frame, spray it with an organic acid solution for 25 to 35 seconds, rinse it with a 2 to 3% hydrochloric acid solution, and finally wash it with deionized water, dry it, transfer it to a treatment solution to react for 10 to 15 minutes, add tris(3-aminopropyl)amine, react for 1.5 to 2 hours, take it out, wash it, and dry it to obtain a semiconductor lead frame.
2. The processing technology of an ultra-thin semiconductor lead frame according to claim 1, characterized in that: The mass ratio of copper, nickel and silicon is 95-97:1.5-2.5:0.
5.
3. The processing technology of an ultra-thin semiconductor lead frame according to claim 1, characterized in that: The organic pickling solution comprises the following substances: 52-56 g / L copper acetate, 50-52 g / L ammonium chloride, 70-74 g / L sodium formate, 8-10 g / L sodium citrate, 20-22 mL / L glacial acetic acid, and 11-12 mL / L formic acid, and the solvent is deionized water.
4. The processing technology of an ultra-thin semiconductor lead frame according to claim 1, characterized in that: The treatment liquid includes the following substances: 30~32g / L 18-mercaptooctadecanoic acid, 15~17g / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 13~15g / L N-hydroxysuccinimide, and the solvent is deionized water: the concentration of the added tris(3-aminopropyl)amine in the treatment liquid is 5~7g / L.
5. The processing technology of an ultra-thin semiconductor lead frame according to claim 1, characterized in that: During the hot rolling process, the final rolling temperature is 700-750° C.; during the cold rolling process, the deformation is 30-40%, and the number of cold rolling is 2 times.
6. The processing technology of an ultra-thin semiconductor lead frame according to claim 1, characterized in that: The amount of the refiner added is 1-2wt% of the total mass of copper, nickel and silicon; the preparation of the refiner comprises the following steps: (1) In an inert gas atmosphere, cerium, magnesium, titanium and aluminum are mixed uniformly, heated to melt, cast, demolded, kept at 400-500°C for 1-2 hours, cooled to room temperature, crushed and ground to obtain alloy particles; (2) mixing polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water, and stirring at 50-70° C. for 2-3 hours to obtain an organic binder; (3) Mix and grind the copper-tungsten alloy, boron trioxide and boron powder, and pass through an 800-mesh sieve to obtain metal powder; (4) spraying the organic binder on the surface of the alloy particles, adding it to the metal powder, mixing, compacting and screening, and repeating the operation until a refiner precursor with a mass ratio of metal powder to alloy particles of 3:7-8 is obtained; (5) The refiner precursor is kept at 80-90°C in an inert gas atmosphere for 1-2 hours, cooled, added to 50-60°C deionized water and soaked for 4-5 hours, dried, kept at 400-450°C in an inert gas flow for 30-40 minutes, and finally sintered at 550-650°C in a vacuum or inert gas atmosphere for 20-40 minutes to obtain the refiner.
7. The processing technology of an ultra-thin semiconductor lead frame according to claim 6, characterized in that: The alloy particles include cerium, magnesium, titanium and aluminum in a mass ratio of 1:3.5-4.5:1.8-2.2:2.5-3.5; the particle size of the alloy particles is 3-5 mm.
8. The processing technology of an ultra-thin semiconductor lead frame according to claim 6, characterized in that: The organic binder includes polyethylene glycol diacrylate, oleic acid, polyethylene glycol, polymethyl methacrylate and deionized water in a mass ratio of 3-5:2-4:18-22:24-26:30; the metal powder includes copper-tungsten alloy, boron powder and boron trioxide in a mass ratio of 75:5-10:15-20.